Interval type-2 fuzzy sets in supplier selection - Turk, Seda; John, Robert; Özcan, Ender (2014)
Selection of an appropriate supplier is a crucial and challenging task in the effective management of a supply chain. This study introduces a model for solving the supplier selection problem using interval type-2 fuzzy sets. Moreover, the influence of the membership function shape on the results obtained from the model has been investigated on a real-world problem instance tackled by Ordoobadi.